Developing TIE “Trigonometry It’s Eazy” Games using Ispring Suite 11 for Trigonometry Learning Media - Nosi Maria Chrisa; Aldila Wanda Nugraha (MultiTech Publisher, 2024)
This development research motivates increasingly rapid technological advances, but educators must correctly use these for medical advances. This can be seen from the need for more innovation in creating exciting learning. Monotonous learning activities confuse students and affect learning outcomes, especially in trigonometry material. This research aims to develop a valid, practical, and effective TIE smartphone game media,